RISCOS DE POLUIÇÃO DE ÁGUAS SUBTERRÂNEAS: UMA PROPOSTA METODOLÓGICA DE AVALIAÇÃO REGIONAL - Foster, Stephen S. D.; Hirata, Ricardo César; Rocha, Gerôncio Albuquerque (Águas Subterrâneas, 1988)
Resumo não disponível.